Evaluating the psychometric properties of a Malay version of Bostick’s (1992) Library Anxiety scale - Abdul Karim, Noor Harun; Ab Rashid, Noor Rashidalila; Abdul Karim, Noor Harun; Ab Rashid, Noor Rashidalila (Malaysian Journal of Library and Information Science, 2016)
The purpose of this study was to identify the components of library anxiety using a Malay version of Bostick’s (1992) Library Anxiety Scale (LAS) and to examine the effects of demographic variables such as gender, native language, year of study, prior exposure to library services and medium of instruction on the variation in the library anxiety construct. A 46-item Malay version of Bostick’s (1992) Library Anxiety Scale (LAS) was tested among 130 medical students drawn randomly from a population of 423 students pursuing their Bachelor of Medicine or Bachelor of Surgery (MBBS) degree. The findings revealed a 3-factor solution which corresponded to the five factors as found by Bostick’s (1992) pioneering psychometric measure of library anxiety. The sub-scales of library anxiety were termed barriers with staff, affective barriers and comfort with library technology. The factor barriers with staff explained 19.76% of the variance in the library construct, followed by affective barriers factor explaining 11.55% of the variance and a third factor comfort with library technology explained 10.282% of the variance. The overall scale as well as each of the three sub-scales was submitted to an internal reliability assessment resulting in a satisfactory Cronbach’s internal reliability coefficient alpha. Despite the fewer number of sub-scales that were yielded by the Malay version of Bostick’s (1992) Library Anxiety Scale (LAS), the translated scale has been shown to be a valid and reliable instrument.